Synthetic niche to modulate regenerative potential of MSCs and enhance skeletal muscle regeneration. (August 2016) - Pumberger, Matthias; Qazi, Taimoor H.; Ehrentraut, M. Christine; Textor, Martin; Kueper, Janina; Stoltenburg-Didinger, Gisela; Winkler, Tobias; von Roth, Philipp; Reinke, Simon; Borselli, Cristina; Perka, Carsten; Mooney, David J.; et al.
Abstract: Severe injury to the skeletal muscle often results in the formation of scar tissue, leading to a decline in functional performance. Traditionally, tissue engineering strategies for muscle repair have focused on substrates that promote myogenic differentiation of transplanted cells. In the current study, the reported data indicates that mesenchymal stromal cells (MSCs) transplanted via porous alginate cryogels promote muscle regeneration by secreting bioactive factors that profoundly influence the function of muscle progenitor cells. These cellular functions, which include heightened resistance of muscle progenitor cells to apoptosis, migration to site of injury, and prevention of premature differentiation are highly desirable in the healing cascade after acute muscle trauma. Furthermore, stimulation of MSCs with recombinant growth factors IGF-1 and VEGF165 was found to significantly enhance their paracrine effects on muscle progenitor cells. Multifunctional alginate cryogels were then utilized as synthetic niches that facilitate local stimulation of seeded MSCs by providing a sustained release of growth factors. In a clinically relevant injury model, the modulation of MSC paracrine signaling via engineered niches significantly improved muscle function by remodeling scar tissue and promoting the formation of new myofibers, outperforming standalone cell or growth factor delivery.